Thin Capitalisation and Firms’ Financial Performance: Evidence from Selected Multinational and Non-Multinational Firms in Nigeria - Osamor, Ifeoma (Acta Universitatis Danubius. Œconomica, 2022)
Absence of thin capitalisation rules in Nigeria and the exploitation of such by multinational and non-multi-national firms is an issue important to shareholders and other stakeholders. Thereby, necessitating the examination of the effects of thin capitalisation on return on invested capital of both multinational and non-multinational firms. Secondary data was obtained from the annual reports of the firms from 2006 to 2020. Thin capitalisation was proxy with debt-to-equity ratio, firms’ financial performance was proxy with return on invested capital, while tax burden and firms’ size were used as control variables. Data was analysed using descriptive statistic, unit root test, co-integration and panel data regression. The findings of this study concluded that thin capitalisation had effects on firms’ financial performance in both multinational and non-multinational firm in Nigeria. Hence, it was recommended that Nigeria government should introduce thin capitalisation rules and other forms of tax avoidance strategies need to be properly checked from both multinational and non-multinational firms to ensure that effective tax rate is paid.